HUBUNGAN PERSEPSI TERHADAP PEMBELAJARAN MATEMATIKA DAN DISPOSISI MATEMATIS DENGAN KEMAMPUAN MENYELESAIKAN SOAL CERITA - Tricahyanti, Wahyu; Astuti, Dwi; Ahmad BS, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to find out the relationship between perception of mathematics learning and mathematical disposition of learners with the ability to solve the story problem of class X-PM2 at SMK Negeri 3 Pontianak. The method used in this research is quantitative method with ex-post facto form. Population in this research is all of student class X of Marketing majors which amounts to 100 people and divided into 3 classes. The sample of this research is 32 students of class X PM 2 SMK Negeri 3 Pontianak. The sampling technique of this research is cluster random sampling. The results showed that there was a positive correlation between perceptions of mathematics learning and the ability to solve story problems with a correlation value of 0.885, there is a positive relationship between mathematical disposition and the ability to solve the story problem with a correlation value of 0.861, there is a positive relationship between perception of mathematics learning and mathematical disposition with a correlation value of 0.907, and there is a positive relationship between the perception of mathematical learning and mathematical disposition with the ability to solve the story problem with a correlation value of 0.896.Keyword:Â Perception of Mathematics Learning, Mathematical Disposition, Ability to Solve the Story Problem